KARAOKE AS A LEARNING STRATEGY IN ENGLISH LANGUAGE TEACHING: AN EXPERIENCE AT IFAL/CAMPUS ARAPIRACA - Torquato Jr., Emiliano; de Andrade Ribeiro, Gabriel; Vitor Bezerra dos Santos, João; Joelson Correia Barros, José; Beatriz Nunes Barbosa, Lara; Henrique de Lima Silva, Pedro; Henrique Santos Mariano, Pedro (Revista Gênero e Interdisciplinaridade, 2026)
The project “Karaoke as a learning strategy in English language teaching: an experience at IFAL/Campus Arapiraca” aims to intervene in the English language teaching and learning process, using karaoke as a form of literacy, favoring student learning and providing teachers with another work alternative to promote critical and inclusive education in the classroom. The project involved students from the integrated computer science and electronics courses from different classes in the first year of vocational high school, who performed in a karaoke event with songs of different styles and eras. Student participation was fundamental to the project’s success, which also aimed to promote cultural identification and personal expression through music. The performances were a talent show with great effort and dedication from the students, who performed choreographies, dressed like true pop stars, and sang in English. The project also highlighted the importance of music in education, promoting essential social, emotional, and cognitive skills for the student’s holistic development. Music was used as a pedagogical tool to enrich student learning and promote collaboration and teamwork. The project is ongoing and will extend until February 2026, with the expectation of continuing to promote the importance of music in education and the development of students. What we present here is an account of the experiences of the project’s organizing team and the students involved.